The relationship between the macroscopic state of electrons and the properties of chorus waves observed by the Van Allen Probes - Chao Yue; Xin An; Jacob Bortnik; Qianli Ma; Wen Li; Richard M. Thorne; Geoffrey D. Reeves; Matina Gkioulidou; Donald G. Mitchell; Craig A. Kletzing (Geophysical Research Letters)
Abstract Plasma kinetic theory predicts that a sufficiently anisotropic electron distribution will excite whistler mode waves, which in turn relax the electron distribution in such a way as to create an upper bound on the relaxed electron anisotropy. Here using whistler mode chorus wave and plasma measurements by Van Allen Probes, we confirm that the electron distributions are well constrained by this instability to a marginally stable state in the whistler mode chorus waves generation region. Lower band chorus waves are organized by the electron β∥e into two distinct groups: (i) relatively large‐amplitude, quasi‐parallel waves with β∥e≳0.025 and (ii) relatively small‐amplitude, oblique waves with β∥e≲0.025. The upper band chorus waves also have enhanced amplitudes close to the instability threshold, with large‐amplitude waves being quasi‐parallel whereas small‐amplitude waves being oblique. These results provide important insight for studying the excitation of whistler mode chorus waves.